Congenital Lower Limb Biphasic Synovial Sarcoma in a Male newborn - Khartoum Teaching Hospital: A Case Report - Mohamadain, Amir A.; Abdalla, Ahmed A. (مجلة الجزيرة للعلوم الصحية; مجلد 9 عدد 2 (2013), 2013)
Synovial sarcoma is a malignant mesenchymal neoplasm which commonly occurs in the extremities of adults. We report on a 12-days-old boy who presented to the department of paediatric surgery at Khartoum teaching hospital with a biphasic synovial sarcoma in the lateral aspect of his left ankle. The tumor was treated with total excision and adjuvant chemotherapy.Histopathologic examination of the excised tumor revealed a biphasic synovial sarcoma. There was no evidence of local recurrence or distant metastasis of the tumor at follow-up examination 24 months postoperatively.